Three dimensional crystallographic orientation relationships for hexagonal close packed structure to face centered cubic structure transformation in pure titanium. (August 2019) - Wei, Bingqiang; Ni, Song; Liu, Yong; Song, Min
Abstract: In this work, two types of stress induced hexagonal close packed structure to face centered cubic structure transformation were observed in cold-rolled pure titanium. The corresponding transformation mechanisms were revealed by high resolution transmission electron microscopy. By using stereographic projections and selected area electron diffraction simulations, the three dimensional orientation relationships for the two types of phase transformation were deduced for the first time. The deduced orientation relationships were also verified by high resolution transmission electron microscopy observations, and the dark side of the basal-type face centered cubic phase was revealed at the atomic scale. Graphical abstract: Unlabelled Image Highlights: Two types of hcp to fcc transformations were characterized at atomic scale by HRTEM. 3-D orientation relationships for hcp to fcc transformation were investigated in Ti. The deduced 3-D orientation relationships were verified by HRTEM observations. A guidance for studying the 3-D morphology of fcc phase in hcp phase was provided.